Developing job performance: mediation of occupational commitment and achievement striving with competence enhancement as a moderator. Issue 2 (25th February 2021) - Lin, Chieh-Peng; Liu, Chu-Mei; Chan, Hui-Ting
Abstract : Purpose: This study draws upon the theory of eudaimonic motivation to develop a model that explains job performance in high-tech industry. This study aims to clarify through what mediating mechanism employees' social interaction and self-efficacy can substantially influence their job performance. At the same time, competence enhancement is examined as a moderator that influences the effects of social interaction and self-efficacy. Design/methodology/approach: The hypotheses developed in this study were empirically tested by collecting three-source data from a leading international business company in Taiwan's high-tech industry. The survey data of this study were first analyzed using confirmatory factor analysis and hierarchical regression analysis for testing the hypotheses of the study. Post hoc tests were then performed using structural equation modeling and bootstrapping analysis for the purpose of double verifications. Findings: This study finds that social interaction and self-efficacy relate to job performance via the full mediation of occupational commitment and achievement striving. Besides, the relationship between social interaction and occupational commitment is positively moderated by competence enhancement, while the relationship between self-efficacy and occupational commitment is negatively moderated by competence enhancement. Originality/value: This work shows important findings that complement previous research on personnel performance and competence. First, this work confirms that social interaction and self-efficacy play critical roles for indirectly influencing job performance through the full mediation of occupational commitment and achievement striving among engineers in high-tech industry. Second, the moderating effects of competence enhancement on the relationships between social interaction and occupational commitment and between self-efficacy and occupational commitment are confirmed by this study.